2017
DOI: 10.1523/jneurosci.3199-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 Is an Astrocyte-Specific Nuclear Marker in the Adult Brain Outside the Neurogenic Regions

Abstract: Astrocytes have in recent years become the focus of intense experimental interest, yet markers for their definitive identification remain both scarce and imperfect. Astrocytes may be recognized as such by their expression of glial fibrillary acidic protein, glutamine synthetase, glutamate transporter 1 (GLT1), aquaporin-4, aldehyde dehydrogenase 1 family member L1, and other proteins. However, these proteins may all be regulated both developmentally and functionally, restricting their utility. To identify a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
257
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(300 citation statements)
references
References 79 publications
20
257
3
1
Order By: Relevance
“…Previous studies in rodents showed that Id3 is only expressed in developing astrocytes (Lamantia, Tremblay, & Majewska, 2014; Molofsky et al, 2013). Sox9 is initially (E8.5–E18.5) expressed in all glial (precursor) cells, and is subsequently downregulated in myelinating oligodendrocytes (Stolt et al, 2003) and becomes astrocyte‐specific (Sun et al, 2017). Also NFIA is initially (E11.5) expressed in all developing glial cells, but downregulates Olig2 and becomes exclusive to astrocytes at E13.5–E16.5 (Deneen et al, 2006; Molofsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rodents showed that Id3 is only expressed in developing astrocytes (Lamantia, Tremblay, & Majewska, 2014; Molofsky et al, 2013). Sox9 is initially (E8.5–E18.5) expressed in all glial (precursor) cells, and is subsequently downregulated in myelinating oligodendrocytes (Stolt et al, 2003) and becomes astrocyte‐specific (Sun et al, 2017). Also NFIA is initially (E11.5) expressed in all developing glial cells, but downregulates Olig2 and becomes exclusive to astrocytes at E13.5–E16.5 (Deneen et al, 2006; Molofsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Following synaptic release, glutamate uptake and degradation are tightly regulated to achieve temporal and spatial signaling specificity and prevent cellular excitotoxicity (Kim et al, 2011; Sattler and Rothstein, 2006; Sheldon and Robinson, 2007). Currently, astrocytes are considered the sole glial cell type that contributes to glutamate uptake and degradation in the CNS (Jayakumar and Norenberg, 2016; Liang et al, 2006; Ortinski et al, 2010; Papageorgiou et al, 2018; Schousboe et al, 2013; Schousboe, 2019; Sun et al, 2017; Tani et al, 2014; Trabelsi et al, 2017; Yuan et al, 2017), as they express high levels of glutamate transporters and glutamine synthetase (GS), an enzyme that converts glutamate into glutamine. In keeping with this view, GS is frequently used as an astrocyte-specific marker (Armbruster et al, 2016; Habbas et al, 2015; Okuda et al, 2014; Papageorgiou et al, 2018; Theofilas et al, 2017; Tong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, GS expression has also been reported in oligodendrocytes (Bernstein et al, 2014; Takasaki et al, 2010), glial cells known for producing myelin and ensheathing axons in the CNS (Pan and Chan, 2017). Although these results remain controversial (Anlauf and Derouiche, 2013; Jayakumar and Norenberg, 2016; Sun et al, 2017), it is of great physiological and clinical importance to identify all potential cellular and molecular components involved in the life cycle of glutamate. GS deletion from the brain results in neonatal death (He et al, 2010), and mutations in the GS gene produce severe neuropathology in humans (Häberle et al, 2012; Spodenkiewicz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies help to identify potential candidates for new and possibly better molecular markers for astrocytes. An interesting addition to the pool of astrocytic markers is SOX9, a transcriptional factor that has been reported as selective for astrocytes in most brain areas (Sun et al, ). This protein is characteristically accumulated in the nuclei of the cells, which sometimes is very useful when, for example, one needs to count astrocytes, which is not a trivial task using antibodies against GFAP that predominantly stain processes, creating a mesh‐like staining pattern.…”
Section: Introductionmentioning
confidence: 99%